Hubungan Tingkat Stres dengan Kualitas Tidur dan Motivasi Belajar pada Mahasiswa Tahun Pertama Fakultas Kedokteran Universitas Sam Ratulangi - Ajhie, Wahyu K.; Marunduh, Sylvia R.; Engka, Joice N. A. (Medical Scope Journal, 2025)
Abstract: The first year of college is a significant period of change that can trigger stress, particularly among medical students. This stress negatively impacts physical and mental health, including sleep quality and learning motivation. This study aims to examine the relationship between stress levels on sleep quality and learning motivation among first-year medical students at Sam Ratulangi University. This quantitative research utilized an observational analytic design with purposive sampling, involving 205 students. Data on stress levels were obtained MSSQ, data on sleep quality were assessed with the PSQI, and data on learning motivation were gathered using the Learning Questionnaire developed by Ariyanti. Data were analyzed using Pearson and Spearman’s correlation test. The majority of respondents experienced high levels of stress, poor sleep quality, and high learning motivation. The correlation test of the relationships between stress level with sleep quality and learning motivation indicated significant relationships (p=0.005; r=0.197 and p=0.002; r=-0.220). In conclusion, there are significant relationships between stress level with sleep quality and learning motivation among first-year medical students at Universitas Sam Ratulangi. The majority of students have high level of stress and poor sleep quality, albeit, they still have high learning motivation. Keywords: stress level; sleep quality; learning motivation Abstrak: Tahun pertama di perguruan tinggi merupakan periode perubahan signifikan yang dapat memicu stres, terutama bagi mahasiswa Fakultas Kedokteran. Stres ini berdampak pada kesehatan fisik dan mental, termasuk kualitas tidur dan motivasi belajar. Penelitian ini bertujuan untuk mengetahui hubungan antara tingkat stres dengan kualitas tidur dan motivasi belajar pada mahasiswa tahun pertama Fakultas Kedokteran Universitas Sam Ratulangi. Penelitian ini menggunakan metode kuantitatif dengan desain observasional analitik dan purposive sampling, yang melibatkan 205 mahasiswa. Data tingkat stres diperoleh menggunakan kuesioner MSSQ, data kualitas tidur menggunakan kuesioner PSQI, dan data motivasi belajar menggunakan Kuesioner Belajar Ariyanti. Data dianalisis menggunakan uji korelasi Pearson dan Spearman’s. Hasil penelitian mendapatkan sebagian besar responden mengalami stres berat, kualitas tidur buruk, dan motivasi belajar tinggi. Uji korelasi hubungan antara tingkat stres dengan kualitas tidur dan motivasi belajar menunjukkan hubungan bermakna (p=0,005; r=0,197 dan p=0,002; r=-0,220). Simpulan penelitian ini ialah terdapat hubungan bermakna antara tingkat stres dengan kualitas tidur dan motivasi belajar pada mahasiswa tahun pertama Fakultas Kedokteran Universitas Sam Ratulangi. Walaupun sebagian besar mahasiswa tersebut mengalami tingkat stres berat dan kualitas tidur buruk, mereka masih memiliki motivasi belajar tinggi. Kata kunci: tingkat stres; kualitas tidur; motivasi belajar